2020
DOI: 10.1002/jor.24759
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic tilt between supine and standing after total hip arthroplasty an RSA up to seven years after the operation

Abstract: The pose of the prosthetic components after total hip arthroplasty (THA) is commonly evaluated on conventional radiographs. Any change of the pelvic position after the operation in supine and between supine and standing position with time will influence validity of the measurements. We evaluated the changed pelvic tilt angle (PTA) in supine and standing position up to 7 years after operation. The aims of our study were (a) to evaluate if the PTA change over time after THA, (b) to assess any difference in PTA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…The Influence of PST and Radiographic Position Babisch et al 32 reported that when using preoperative radiographs to inform the placement of the acetabular component, surgeons should note the dynamic change of PST and effect on postoperative acetabular alignment, which could decrease the occurrence of adverse outcomes, such as the dislocations in our study. 17,22,33,34 Routinely, the observation of the pelvis is determined by radiographs in the supine position in perioperative period, 17 and the measurement of PST from a single supine film is valid and reliable for evaluating the pelvic position. 17,26,[33][34][35] In addition, AP pelvic radiographs remain the standard of care imaging modality for pre and postoperative assessment during THA owing to easy accessibility, cost effectiveness, low radiation exposure, and widespread availability, 18,26,33,36 and the use of AP radiographs to assess changes in pelvis has been validated, 34,37 which proved that the position and radiographic methods we used in this study was appropriate.…”
Section: Time Of Change In Pstmentioning
confidence: 99%
See 4 more Smart Citations
“…The Influence of PST and Radiographic Position Babisch et al 32 reported that when using preoperative radiographs to inform the placement of the acetabular component, surgeons should note the dynamic change of PST and effect on postoperative acetabular alignment, which could decrease the occurrence of adverse outcomes, such as the dislocations in our study. 17,22,33,34 Routinely, the observation of the pelvis is determined by radiographs in the supine position in perioperative period, 17 and the measurement of PST from a single supine film is valid and reliable for evaluating the pelvic position. 17,26,[33][34][35] In addition, AP pelvic radiographs remain the standard of care imaging modality for pre and postoperative assessment during THA owing to easy accessibility, cost effectiveness, low radiation exposure, and widespread availability, 18,26,33,36 and the use of AP radiographs to assess changes in pelvis has been validated, 34,37 which proved that the position and radiographic methods we used in this study was appropriate.…”
Section: Time Of Change In Pstmentioning
confidence: 99%
“…17,22,33,34 Routinely, the observation of the pelvis is determined by radiographs in the supine position in perioperative period, 17 and the measurement of PST from a single supine film is valid and reliable for evaluating the pelvic position. 17,26,[33][34][35] In addition, AP pelvic radiographs remain the standard of care imaging modality for pre and postoperative assessment during THA owing to easy accessibility, cost effectiveness, low radiation exposure, and widespread availability, 18,26,33,36 and the use of AP radiographs to assess changes in pelvis has been validated, 34,37 which proved that the position and radiographic methods we used in this study was appropriate. And radiographic overlap could occur in a lateral position between right and left hips, making the diagnostic evaluation complicated and less efficient.…”
Section: Time Of Change In Pstmentioning
confidence: 99%
See 3 more Smart Citations